2021
DOI: 10.3390/v13122535
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ribavirin on Mumps Virus Population Diversity

Abstract: Frequent mumps outbreaks in vaccinated populations and the occurrence of neurological complications (e.g., aseptic meningitis or encephalitis) in patients with mumps indicate the need for the development of more efficient vaccines as well as specific antiviral therapies. RNA viruses are genetically highly heterogeneous populations that exist on the edge of an error threshold, such that additional increases in mutational burden can lead to extinction of the virus population. Deliberate modulation of their natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In the current study, the treatment of FVSKG2 with 0.025 mM ribavirin for series of five passages could not induce any mutations in the 1,898 base pairs of viral genome sequenced, which is in disagreement with previous studies where antiviral activity of ribavirin on ssRNA viruses, viz. FMDV, HCV, polio virus, hepatitis E virus and mumps virus was found to be due to mutagenic action of ribavirin ( 20 , 32 , 39 , 56 , 57 ). The reasons for no-mutagenic action of ribavirin on FVSKG2 may be due to variable reasons: (a) dsRNA are reported to be less prone to mutations than ssRNA viruses ( 58 ), (b) Sequencing only a part of viral genome, and (c) using sanger’s sequencing method which cannot detect the sub-consensus variants that could have likely generated during the treatment of virus with 0.025 mM ribavirin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the treatment of FVSKG2 with 0.025 mM ribavirin for series of five passages could not induce any mutations in the 1,898 base pairs of viral genome sequenced, which is in disagreement with previous studies where antiviral activity of ribavirin on ssRNA viruses, viz. FMDV, HCV, polio virus, hepatitis E virus and mumps virus was found to be due to mutagenic action of ribavirin ( 20 , 32 , 39 , 56 , 57 ). The reasons for no-mutagenic action of ribavirin on FVSKG2 may be due to variable reasons: (a) dsRNA are reported to be less prone to mutations than ssRNA viruses ( 58 ), (b) Sequencing only a part of viral genome, and (c) using sanger’s sequencing method which cannot detect the sub-consensus variants that could have likely generated during the treatment of virus with 0.025 mM ribavirin.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were rinsed and replenished with 100 μL growth medium containing one of the four concentrations of mutagens (0, 0.5, 1.0, and 1.5 mM) in three replicates. To determine cell viability at specific time point, cells were incubated at 37°C and 5% CO2, as described in the previous study ( 35 , 39 ). At 24 hpt and 48 hpt the growth medium of the cells was replaced with 100 μL of DMEM containing MTT at a concentration of 0.5 mg/mL and incubated for 4 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Among them, linsitinib has been reported to have potent antitumor activity in diffuse midline glioma when combined with modified chimeric antigen receptor T-cells ( de Billy et al, 2021 ); GSK1904529A has also been found to inhibit glioma tumor growth, induce apoptosis, and inhibit migration ( Zhou et al, 2015 ), and AZD9496; and SR16157 are potential drugs for treating breast cancer that are present in the early stages of clinical research ( Zhang et al, 2021 ) ( Rausch et al, 2011 ). GCH1 is sensitive to ribavirin, a synthetic nucleoside analogue with broad antiviral activity ( Jurković et al, 2021 ). EGFR was sensitive to the small-molecule rearranged inhibitor BLU667 ( Subbiah et al, 2018 ), the tyrosine kinase inhibitor dasatinib ( Vitali et al, 2009 ), and the Bruton’s tyrosine kinase (BTK) inhibitor spebrutinib during transfection ( Kaliamurthi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%